Desarrollo de un sistema informático para la gestión de información y revisión de trabajos de investigación del congreso internacional de comunicación emergente de la Universidad Técnica de Cotopaxi utilizando lean software Development. - Aranda Guapi, Patricia Brigitte (2023)
Currently, the successful development of congresses involves several critical activities, such as the dissemination of information and the review of research papers, these activities are of great relevance because they merge science, technology, education and communication, promoting interaction and knowledge exchange. Although social networks have revolutionized the promotion of congresses, the control of information remains a constant challenge, in addition, another limitation is the review of research papers, a process that used to be done by e-mail, which often led to delays, follow-up problems and confusion. In this context, the lack of centralization and efficiency in the management of information and review of research papers in the Communication career at the Technical University of Cotopaxi has had a negative impact on the quality of the congresses developed. In order to overcome these challenges, the technological proposal is to develop a computer system to manage information and review of papers, optimizing communication and facilitating decision making. Following the principles of the Lean Software Development methodology, the system aims to optimize existing processes to provide a more satisfactory experience to the organizers, participants and exhibitors of the International Congress of Emerging Communication. To achieve this, web development tools such as CodeIgniter, Bootstrap, HTML, JavaScript, CSS and MySQL will be used. The implementation of this system will provide an efficient and modern solution for the integral management of the congress, thus contributing to the improvement of the quality and scope of this event of great academic and scientific importance